ASSESSMENT OF COMPETITIVE CONFRONTATION BETWEEN CHINA AND THE USA IN THE GLOBAL MARKET - Mirolyubova, Olga; Schislyaeva, Elena (International Journal of Economic Practice and Policy, 2015)
Competition between US and China on global oil market has specific differences and long lasting history. Contradictions of China and the United States developed in the situation with the Crimea. The article reflects the confrontation in the political and economic sphere, as well as the trends in the development of relations between countries. Authors have applied the methods of analysis, historical method and synthesis in the research.
Keywords: globalization; economic growth; policy of investment; international crisis; resources; political situation